Personality differences and psychological variables related to the risk of eating disorders - Castejón Martínez, María Ángeles; Berengüi, Rosendo (Anales de Psicología / Annals of Psychology, 2020)
Certain psychological variables and personality are considered as predisposing or influential factors for the subsequent development of eating disorders. Also the implementation of some risk behaviors, such as binge eating, vomiting or excessive physical exercise for weight loss. The objective of the study was to compare the differences in personality and relevant psychological variables related to eating disorders, in women and men, based on compliance with specific criteria to help identify individuals with potential eating disorders. Participants were 604 university students. The Eating Disorder Inventory-3 (EDI-3) and referral form (EDI-3 RF), and the Five-Factor Inventory (NEO-FFI) were used. The results showed that up to 58.5% of women and 49.5% of men met remission criteria. In both women and men, there are differences between groups with criteria and those who do not, mainly in neuroticism, drive for thinness, bulimia, body dissatisfaction and asceticism. The scores in the neuroticism factor and in the great majority of psychological scales are also higher in the subjects that accomplish the highest number of criteria.